2016
DOI: 10.1097/jcn.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Heart Failure–Specific Health Literacy Scale

Abstract: Our new HL scale was demonstrated to be a reliable, valid instrument for measuring functional, communicative, and critical HL in patients with HF. Exploring a patient's HL level, including the ability to access, understand, and use health information as well as the ability to read and write, may provide better understanding of patients' potential barriers to self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
(30 reference statements)
0
25
0
2
Order By: Relevance
“…Older caregivers also showed a decrease in the reading skills. These results suggest that it would be appropriate to undertake educational programmes aimed at increasing the levels of health literacy of this particular category of caregivers, as suggested for patients (Matsuoka, Kato et al., ; Matsuoka, Tsuchihashi‐Makaya et al., ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Older caregivers also showed a decrease in the reading skills. These results suggest that it would be appropriate to undertake educational programmes aimed at increasing the levels of health literacy of this particular category of caregivers, as suggested for patients (Matsuoka, Kato et al., ; Matsuoka, Tsuchihashi‐Makaya et al., ).…”
Section: Discussionmentioning
confidence: 78%
“…Second, despite participant enrolment in five hospitals, the sample cannot be considered representative of all Italian caregivers’ population. Third, most of the tools used to assess HL (including S‐TOFHLA) do focus only on a specific domain of HL, the functional one (Matsuoka, Kato et al., ; Matsuoka, Tsuchihashi‐Makaya et al., ) while, according to Nutbeam (), the concept of health literacy includes three domains: functional (the ability to read and write), communicative (the ability to gather and transmit information) and critical (the ability to critically examine information).…”
Section: Discussionmentioning
confidence: 99%
“…In the German version, this item reportedly represents a confusing phrase relating to either self‐collected information or information received from doctors . Matsuoka et al recently reported that this item should be replaced with a communicative factor rather than a critical factor. Item 11 may need to be considered further in future psychometric studies of the HLS.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this poor association might be because existing instruments of health literacy are too general to capture wide ranges of abilities specific to medication use [ 20 ]. Although some health literacy instruments (e.g., either general health literacy [ 12 ], disease-specific [ 30 , 31 , 32 , 33 , 34 , 35 ], or having certain related domains [ 36 , 37 , 38 ]) are available, none of these instruments/measures or domains are specifically designed to assess the levels of medication-related health literacy. A few instruments have been developed to assess levels of medication-related health literacy, including the 14-item Medication Literacy Assessment (MedLitRxSE) [ 39 ], 20-item Numeracy Understanding in Medicine Instrument (NUMi) [ 40 ], 21-item Montana State University Complementary and Alternative Medicine (MSU CAM) Health Literacy [ 41 ], and 6-item Medication Health Literacy Measure (MHLM) [ 42 ]; the application of these instruments is restricted due to their limited domains covered.…”
Section: Introductionmentioning
confidence: 99%